АРТЕРИАЛЬНЫЙ ПРОТОК У ГЛУБОКОНЕДОНОШЕННЫХ НОВОРОЖДЕННЫХ: КЛИНИКО-МОРФОЛОГИЧЕСКАЯ ХАРАКТЕРИСТИКА - Сарыева, Ольга Павловна; Харламова, Наталья Валерьевна; Кулида, Людмила Викторовна; Фисюк, Юлия Андреевна (FORCIPE, 2022)